Globalization and the welfare state - Mishra, Ramesh Dr (Edward Elgar, 1999)
Does globalization mean a race to the bottom in social standards and the inevitable decay of the welfare state? Ramesh Mishra - a leading authority on social policy - examines the implications of globalization in respect of social policy and social standards in advanced industrial countries. Globalization is a form of international neo-liberalism supported by the United States, world markets and organizations such as the IMF and OECD. This book considers its impact on full employment and the labour market, income distribution, taxation and social protection in developed capitalist countries. It argues that social standards have declined far more in English-speaking countries than in continental Europe and Japan, and that globalization is as much a political and ideological phenomenon as it is an economic one. In conclusion, it argues the case for a transnational approach to social policy to ensure that social standards rise in line with economic growth. Globalization and the Welfare State is highly accessible and will be welcomed by students and scholars of social policy, social work, political science and sociology as well as by policymakers in international organizations and government